Policy options for low-carbon sustainable transport systems in Kathmandu Valley, Nepal: A survey-based study - Jyoti Prajapati; Maheswar Rupakheti; Mark G. Lawrence (Transportation Research Interdisciplinary Perspectives)
Mobility and transport activities have increased significantly over the past few decades in the Kathmandu Valley, a metropolitan region in Nepal and one of the fastest-growing cities in South Asia. In order to identify the low carbon sustainable transport (LCST) policy measures that fit the local context, we investigated the perceptions of stakeholders with a background and interest in the local transport system. The study is guided by the ‘avoid-shift-improve (ASI)’ approach and involves two rounds of consultation with key stakeholders using the Delphi method to carefully examine the local conditions and select potential policy options. We found that the stakeholders considered cost-effective planning, regulatory and technological ASI measures (e.g., integrating transport systems, vehicle inspection and maintenance, tax rebates, promoting electric vehicles and public buses) as the most preferred policies and of the highest importance. In contrast, financial (e.g., increasing tax and fuel price) and highly technological measures were considered moderately or least-preferred policies. The identified combination of policy options is expected to be suitable for developing a LCST system in the local context of the Kathmandu Valley, offering several co-benefits, including reduced emissions of harmful air pollutants and greenhouse gases, as well as improved social equity and economic development. The approach demonstrated here can be useful as a model for other developing cities in South Asia and elsewhere.